Mycosis fungoides: association of KIR ligands and HLA‐DQB1*05 with bad prognosis of the disease. (9th March 2015) - Brazzelli, V.; Rivetti, N.; Badulli, C.; Carugno, A.; Cananzi, R.; De Silvestri, A.; Martinetti, M.; Borroni, G.
Abstract: Background: Mycosis fungoides (MF) is the most common cutaneous T‐cell lymphoma. We previously reported that the prognosis of MF patients is not only related on clinical variables but it is also associated with peculiar HLA alleles. Until today, the association of HLA ligands for KIR with the prognosis of the disease has not yet been analysed. Objective: We investigated the frequency of HLA ligands for killer cell Immunoglobulin‐like receptors (KIRs) in MF patients, evaluating if the presence of particular HLA alleles that are ligands for KIR may have prognostic value. Methods: The study includes 46 Caucasian MF patients that, between 1993 and 1997, underwent HLA genomic typing. All patients were diagnosed and followed up from 1977 to 2012 (mean follow‐up of 11 years). Results: MF patients have been divided into two groups (long survivors and dead patients). We noticed that the HLA‐Bw6/Bw6 specificity increased among the group of seven dead patients compared to the group of 39 long survivors (71.4% vs. 41.0%, P = ns, OR = 3.59), while in the long survivors group the HLA‐ Bw4/Bw4 specificity increased when compared to dead patients (23.0% vs. 0%, P = ns). Moreover, we observed that six of the seven dead patients had HLA‐DQB1*05; the phenotypic frequency of this HLA allele, in dead and long survivors patients, was 85.7% and 23.0% respectively ( P = 0.004; OR = 20). Conclusion: Our observations suggest that the presence of the HLA‐DQB1*05 alleles characterizes the patients with the poorest prognosis in MF. In addition, absence of the KIR‐ligand epitope HLA‐B Bw4 showed a trend of being more prominent in MF patients with the poorest prognosis.